Distributed leadership in Chilean schools: challenges in a pandemic context - Ahumada, Luis (2024)
The COVID-19 pandemic meant great stress and challenges for schools. In this context, distributed leadership emerged as a timely and relevant approach to understanding the changes that the school must adopt. In this research, through semi-structured interviews carried out with directors of 5 schools, we delved into how the pandemic was faced, the actions that were carried out, who was involved, the learning and projections. The results show that teachers and the psychosocial team appeared as relevant actors. The link with parents and students, who require socio-emotional or technical support associated with the use of the virtual teaching and learning methodology, appeared as another relevant aspect.